HJURP modulates cell proliferation and chemoresistance via the MYC/TOP2A transcriptional axis in gastric cancer - Li, Xu; Li, Xiwen; Ren, Yanlin; Wang, Ling; Mao, Zehao; Gao, Shikun; Ma, Peng; Chen, Junjie (Frontiers in Molecular Biosciences, 2025)
BackgroundThe histone chaperone Holliday Junction Recognition Protein (HJURP) has been associated with multiple types of cancers, but its role in GC is not yet fully understood. Considering its functions in centromere stability and DNA repair, investigating HJURP’s role in GC may offer novel therapeutic perspectives.MethodsHJURP expression was examined in a dataset comprising TCGA-STAD samples and an internal group of GC patients, utilizing RNA sequencing and Western blot techniques. Functional experiments were carried out on the AGS and HGC-27 GC cell lines. The expression levels of HJURP, MYC, and Topoisomerase II alpha (TOP2A) were assessed via quantitative real-time PCR and Western blot. Proliferation rates of the cells were determined through EdU, CCK-8, and colony formation assays.ResultsCompared to adjacent normal tissues, HJURP expression was notably increased in GC tissues, a finding consistent across both the TCGA-STAD database and our internal patient group. Silencing HJURP markedly reduced GC cell growth and chemoresistance. Mechanistically, HJURP enhanced MYC stability, which in turn promoted TOP2A transcription. Rescue experiments confirmed that overexpression of TOP2A alters proliferation and chemoresistance of GC cells with HJURP knockdown, indicating the dependency of this axis on MYC activity.ConclusionOur study demonstrates that HJURP is critical for promoting GC proliferation and chemoresistance through the regulation of the MYC/TOP2A transcriptional network. Targeting HJURP might offer a novel therapeutic avenue for GC, necessitating further exploration of its clinical potential. This work underscores the value of investigating histone chaperones as potential targets in cancer treatment.